Analisa Variasi Jumlah Uap terhadap Efisiensi Ketel Uap di PT. Bukit Barisan Indah Prima (BBIP) Grup Kabupaten Muaro Jambi - Firdaus, Aneka; Gunawan, Gunawan; Saputra, M. A. Ade; Abror, Rifki (Jurnal Rekayasa Mesin, 2024)
Power plant steam that is in palm oil factory PT. Bukit Barisan Indah Prima (BBIP) Group only use 1 unit of a steam boiler with type Takuma N-750 SA water tube boiler. On their work this final analysis variations in the quantity of steam against efficiency boiler PT. Bukit Barisan Indah Prima (BBIP) grup Muaro Jambi District, Jambi. In this research used method of direct to know the efficiency boiler on various variations in the quantity of steam. The results from the study efficiency lowest acquired at the number of steam 14 ton/hour and the amount of fuel used of 2.730 kg/hour then efficiency boiler of 83,87 % and efficiency highest acquired at the number of steam 18 tons/hour and the amount of fuel used of 3.510 kg/hour then efficiency boiler of 85,14 %.